2006
DOI: 10.1177/070674370605100402
|View full text |Cite
|
Sign up to set email alerts
|

The Lay Concept of Conduct Disorder: Do Nonprofessionals Use Syndromal Symptoms or Internal Dysfunction to Distinguish Disorder from Delinquency?

Abstract: The dysfunction requirement appears to reflect a widely shared lay and professional concept of disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…As family members are normally the gateway to engagement of their children in treatment, future studies might explore the influence of context on their judgments of treatment effectiveness. For judgments of the existence of mental disorder, research has demonstrated that laypersons often make similar distinctions as professionals (Wakefield et al 2006;Garb 1998;Marsh et al 2014), and some scholars think that the similarities may reflect general reasoning processes (Marsh et al 2014). From these findings, we expect that parents may be equally sensitive to the importance of context for making judgments about treatment.…”
Section: Iqr Interquartile Rangementioning
confidence: 95%
See 1 more Smart Citation
“…As family members are normally the gateway to engagement of their children in treatment, future studies might explore the influence of context on their judgments of treatment effectiveness. For judgments of the existence of mental disorder, research has demonstrated that laypersons often make similar distinctions as professionals (Wakefield et al 2006;Garb 1998;Marsh et al 2014), and some scholars think that the similarities may reflect general reasoning processes (Marsh et al 2014). From these findings, we expect that parents may be equally sensitive to the importance of context for making judgments about treatment.…”
Section: Iqr Interquartile Rangementioning
confidence: 95%
“…Existing research offers evidence that experienced clinicians are sensitive to the social context surrounding adolescent antisocial behavior, and that they judge youth as less likely to have a mental disorder when context suggests the behavior might be a normal reaction to a harsh environment, rather than irrational responses resulting from internal dysfunction (Hsieh 2001;Hsieh andKirk 2003, 2005;Pottick et al 2003Pottick et al , 2007Wakefield et al 2002Wakefield et al , 2006. Other research studies have found that clinicians differentially use contextual information to weigh the importance of symptoms in judging whether a youth should be considered as having a diagnosis of conduct disorder (De Los Reyes and Marsh 2011;Marsh et al 2016), and have demonstrated that contextual information not only influences how clinicians arrive at diagnoses, but can also influence their judgments about other aspects of the clinical encounter, such as prognosis, need for professional help, and appropriateness of medication .…”
mentioning
confidence: 99%
“…Wakefield et al. () looked at vignettes administered to social work graduate students, laypeople, and clinicians to assess judgments of a White or Mexican youth with antisocial behaviors. By adjusting text to explain behavior as either an environmental reaction or an internal dysfunction, the team found ethnicity/race differences in the impact of context on judgments of whether or not the youth had the disorder (Wakefield et al.…”
Section: Introductionmentioning
confidence: 99%
“…Green et al (2007) reported on the use of vignettes administered through an Internet-based tool and using implicit association tests (IATs) (Project Implicit, Harvard; http://www.implicit.harvard.edu), finding that while most physicians did not admit to explicit racial preference, many showed implicit preference for White patients that predicted differences in their treatment recommendations. Wakefield et al (2006) looked at vignettes administered to social work graduate students, laypeople, and clinicians to assess judgments of a White or Mexican youth with antisocial behaviors. By adjusting text to explain behavior as either an environmental reaction or an internal dysfunction, the team found ethnicity/race differences in the impact of context on judgments of whether or not the youth had the disorder (Wakefield et al 2006).…”
mentioning
confidence: 99%
“…Particularly when symptoms occur without preceding life events, labeling as mental illness is no necessary precondition for perceiving a need for professional help. Similar disparities in lay judgments of illness status and need-for-help judgments have also been reported for conduct disorders [21]. This is an important point as it helps separate issues of service provision from the necessity of a diagnosis, at least if looked at it from a lay perspective.…”
Section: Discussionmentioning
confidence: 53%